The influence of mechanochemical and microwave modification on the properties of SnO2 as photocatalyst - Samsonenko, Mariia M.; Khalameida, Svitlana V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
Samples of precipitated SnO2 were modified by means of mechanochemical and microwave treatment. Physicochemical properties of all samples were investigated using DTA, XRD, FTIR spectroscopy, nitrogen adsorption-desorption and UV-Vis spectroscopy. Photocatalytic activity was evaluated using the degradation of rhodamine B and safranin T under Vis-irradiation. It was found that the initial precipitated and modified samples correspond to the composition of tin oxyhydroxide - SnO(OH)х. It has been established that as a result of mechanochemical and microwave treatment of tin oxyhydroxide in the wet gel stage, it is possible to obtain photocatalytically active materials with a uniform mesoporous structure and high specific surface values and a band gap of about 3.5-3.6 eV. A peculiarity of the mechanochemical treatment of xerogels in water is the formation of a meso-macroporous structure. Relationship between physicochemical and photocatalytic properties of prepared samples has been discussed. The dependence of the efficiency of photocatalytic degradation of dyes on changes in the porous structure, the presence of defects on the surface of the catalyst, and its electronic characteristics was established.